2021
DOI: 10.1016/j.talanta.2020.121862
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Covid-19 antiviral drugs in biological fluids and tissues

Abstract: Since coronavirus disease 2019 (COVID-19) started as a fast-spreading pandemic, causing a huge number of deaths worldwide, several therapeutic options have been tested to counteract or reduce the clinical symptoms of patients infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Currently, no specific drugs for COVID-19 but many antiviral agents have been authorised by several national agencies. Most of them are under investigation in both preclinical and clinical trials; however, pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 164 publications
(239 reference statements)
0
31
0
Order By: Relevance
“…In addition, this is also important because increases in misinformation about vaccines may also limit or influence the acceptance, and with the pandemic emergency of COVID-19, there has been the shifting of healthcare resources with the accumulation of susceptible individuals and a higher likelihood of vaccine-preventable diseases outbreaks. Furthermore, it should be pointed out that the evaluation of vaccination depends on used methods, therefore, it is important to refer to the detection and quantification of corresponding pharmaceuticals [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this is also important because increases in misinformation about vaccines may also limit or influence the acceptance, and with the pandemic emergency of COVID-19, there has been the shifting of healthcare resources with the accumulation of susceptible individuals and a higher likelihood of vaccine-preventable diseases outbreaks. Furthermore, it should be pointed out that the evaluation of vaccination depends on used methods, therefore, it is important to refer to the detection and quantification of corresponding pharmaceuticals [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the facts mentioned above, the development of suitable analytical methodologies for the determination of promising antiviral agents used for COVID 19, such as favipiravir, is strongly required not only for routine quality control in pharmaceutical formulations but also to support pharmacokinetic and metabolic studies in biological samples of both human and animal origin. Apart from these requirements, such studies in biological matrices will assist in the development of new drugs [ 16 ]. Survey of the literature revealed that only two studies have been made on the quantification of favipiravir by using high performance liquid chromatography coupled with ultraviolet (UV) detection [ 17 ], and spectrofluorimetric method [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are also varied statistical methods used for the analysis such as chi-square test, t -test, Wilcoxon, Fisher’s exact, two-tail tests, correlation coefficient, p -values, etc. For the same reasons, analytical procedures, e.g., from sample pre-treatment to separation, detection, and quantification (e.g., [ 81 ]), were not investigated in the present study. Additionally, few studies were found in the literature linking heavy metal toxicity to the occurrence of non-communicable diseases in PLWHIV, and all the studies included in the review are cross-sectional and lack the strength to evaluate causality.…”
Section: Discussionmentioning
confidence: 99%